Pobreza, inserción precaria e ineficiencia social. (2021)
The poverty is a social phenomenon that has been object of study of innumerable analysis of multilateral and national agencies and investigations done in academic spaces; however, there are still theoretical and methodological difficulties for an appropriate approach to this phenomenon. This paper contributes to the conceptual discussion about poverty, for this purpose, it confronts the traditional notion of lack of material goods with a perspective that emphasizes in the relational dimension, and it concludes that poor people are characterized by facing conditions of precarious insertion to the economic, social and politic life, which constitutes itself as a situation of social isolation.